Morphological and molecular characterization of adult worms of Leucochloridium paradoxum Carus, 1835 and L. perturbatum Pojmańska, 1969 (Digenea: Leucochloridiidae) from the great tit, Parus major L., 1758 and similarity with the sporocyst stages. Issue 4 (December 2014) - Rząd, I.; Hofsoe, P.; Panicz, R.; Nowakowski, J.K.
Abstract Unlike the sporocyst stages, adult leucochloridiid digeneans are difficult to differentiate. Sporocyst broodsacs can be identified on the basis of their colour and banding pattern, but in the absence of broodsacs and when experimental infection cannot be performed, tentative morphological identification needs to be verified, and molecular techniques offer a tool to do this. In this study, adult leucochloridiid digeneans were collected from the great tit (Parus major) found dead at three localities at or near the Baltic Sea coast (Hel, Bukowo-Kopań and Szczecin) in northern Poland. On the basis of differences in their morphological characters, Hel specimens were tentatively assigned to Leucochloridium perturbatum, Bukowo-Kopań and Szczecin specimens being identified tentatively as L. paradoxum. Subsequent ribosomal DNA sequence analysis confirmed the identification of these leucochloridiid flukes. Nucleotide sequences discriminating between the two species were identical to those used by earlier authors as characteristic of two distinctly different sporocyst broodsacs representing L. perturbatum and L. paradoxum.